Are we heading toward a single-payer system? - Case, Ingrid (Benefits Selling. Breaking News, 2014)
Legislators briefly considered single-payer coverage in the United States during the health care debates, but ultimately settled on the hybrid public/private solution that is the Patient Protection and Affordable Care Act. [...]the subject of a single-payer system -- one in which the government, rather than private insurance companies, pays all health care costs -- has not disappeared.